(untitled) (Indian Journal of Nematology, 2024)
Organic supplements viz. vermicompost, leaf waste, crop residue, FYM, enriched organic substance alone and with carbofuran were investigated against Meloidogyne incognita on brinjal in green house conditions. Nematode development was observed to decrease in application of organic substances alone except P enriched sources. Along with carbofuran and organic substances there was also reduction in nematode galls, however this reduction in number of galls was lower at higher dose of carbofuran. Plant biomass was much lower in the single treatments than the combined treatments over inoculated control.